LEGAL PROTECTION EFFORTS BY NOTARIES IN BACKDOOR LISTING PRACTICES AS CORPORATE ACTIONS IN THE CAPITAL MARKET - Hafidah Nur Epsteinnia; Dona Budi Kharisma; Ayub Torry Satriyo Kusumo (RADJA PUBLIKA, 2026)
Backdoor listing is a method used by companies to enter the capital market without going through the lengthy and costly initial public offering (IPO) process. This practice typically involves the acquisition of a public company by a private company, allowing the private company to be listed on the stock exchange through the acquired public company. One of the main requirements for listing shares on the stock exchange is that the business must be a limited liability company. In this context, notaries play a crucial role in ensuring legality and compliance with applicable regulations. Legal protection for notaries in backdoor listing practices is crucial given the complexity and potential legal risks involved. Notaries must ensure that all documents and processes related to backdoor listing comply with the Limited Liability Company Law (UUPT), the Capital Market Law (UUPM), and other relevant regulations. However, due to the lack of detailed legal regulations regarding backdoor listing in Indonesia, notaries must exercise caution and ensure that every step taken complies with applicable legal principles.